The prospective contribution of LPG in the entire energy grid for the sustainable development of Bangladesh - Beauty, Farzana Yasmin (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.